2014
DOI: 10.1080/09168451.2014.905179
|View full text |Cite
|
Sign up to set email alerts
|

1-Kestose consumption during pregnancy and lactation increases the levels of IgA in the milk of lactating mice

Abstract: To examine the effect of dietary supplementation with 1-kestose on the IgA levels in milk, BALB/c mice were fed diets with or without 5% 1-kestose during pregnancy and lactation. The total and specific IgA levels in the milk were measured at 7 and 14 days after delivery. A two-way ANOVA with repeated measures resulted in a significant effect of 1-kestose-supplementation on total IgA concentrations (p < 0.05) and the level of anti-Bacteroides IgA (p < 0.05). A significant positive correlation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…as well as the total IgA concentration in both the intestine and milk in mice, and the IgA concentration in milk was correlated with the number of gut Bacteroides spp. [39]. In the present study, however, the IgA concentration in the colostrum did not differ between the groups [23].…”
Section: Discussioncontrasting
confidence: 66%
“…as well as the total IgA concentration in both the intestine and milk in mice, and the IgA concentration in milk was correlated with the number of gut Bacteroides spp. [39]. In the present study, however, the IgA concentration in the colostrum did not differ between the groups [23].…”
Section: Discussioncontrasting
confidence: 66%
“…Our recent in vitro study using several oligosaccharides and lactobacilli suggested that 1-kestose content was crucial for prebiotic activity in FOS [10]. On the other hand, in vivo studies using 1-kestose are quite limited; supplementation with 1-kestose in the diet for pregnant and lactating mice increased the IgA levels in maternal milk [11]. Oligosaccharides are usually metabolized in gut microbiota, resulting in accumulation of short-chain fatty acids (SCFA), which have various beneficial effects on the host [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although many reports have indicated that IgA increases in the large intestine after FOS intake [19], the influence of the FOS intake on salivary IgA remains unclear. Our previous study indicated that ingestion of FOS and a mixture of polydextrose and lactitol for three weeks increased IgA levels in both the large intestine and the saliva of rats and was the first to demonstrate the interrelationship between ingestion of indigestible carbohydrates and salivary IgA levels [20].…”
Section: Introductionmentioning
confidence: 99%